INFLUENCE OF CULTURAL FACTORS ON AIRMEN’S PROFESSIONAL ACTIVITY IN MULTICULTURAL COMPANIES - Пазюра, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article is an investigation into miscommunications between air traffic controllers and pilots. Miscommunications may broadly be applied to a range of verbal communications problems ranging from misunderstandings, such as those due to ambiguity, language structure, to more technical problems. The author stresses that those misunderstandings may be due to cultural differences. Studies indicate that miscommunication is a pervasive problem in air traffic control and, although infrequent when considered as a percentage of daily transactions, nevertheless, has been a causal factor in numerous fatal accidents